123 Empowering Patients after Stroke: Development of a Stroke Information Booklet. (16th September 2019) - Dennehy, Karen; Synnott, Padraig; Murphy, Robert; Galvin, Patricia; Canavan, Michelle; Walsh, Thomas; O' Donnell, Martin
Abstract: Background: Patient involvement in healthcare is key to the provision of patient centred care. The national patient experience survey 2018 found that up to 40% of patients did not get adequate information about their condition after discharge.(1) As the planning phase in introducing a stroke information booklet, we sought to examine what patients, families and healthcare professionals feel are important components in such an information booklet. Methods: We performed a cross sectional cohort study. A questionnaire was developed after a panel discussion among physicians, allied health professionals, and clinical nurse specialists about what would be important facets to include. Thirteen items were shortlisted and assessed using a Likert scale. Results: There were 76 respondents to the questionnaire including nurses (17), allied health professionals (13), doctors (28), stroke patients (10) and relatives (8). Items viewed as most important to include were: an introduction to stroke, future stroke risk, and effects of stroke on daily life. Items viewed as least important to include were - an overview of medical treatments for stroke and information on equipment needs post stroke. A Mann Whitney U test found that patients/families rated information about future stroke risk as more important to include than healthcare professionals (p=0.021). Free text found that psychological effects of stroke, and sexual health post stroke were commonly suggested. Conclusion: Patients/Families are keen to receive information regarding stroke, particularly about future risk of stroke. Empowering patients with information about stroke that is relevant to them and their care providers is a fundamental part of secondary stroke prevention. We also need to focus more on the psychological impact of stroke. Our booklet will incorporate information we have gathered in this study to make it a truly patient centred resource.